2022
DOI: 10.3390/pharmaceutics14081659
|View full text |Cite
|
Sign up to set email alerts
|

PSME4 Degrades Acetylated YAP1 in the Nucleus of Mesenchymal Stem Cells

Abstract: Intensive research has focused on minimizing the infarct area and stimulating endogenous regeneration after myocardial infarction. Our group previously elucidated that apicidin, a histone deacetylase (HDAC) inhibitor, robustly accelerates the cardiac commitment of naïve mesenchymal stem cells (MSCs) through acute loss of YAP1. Here, we propose the novel regulation of YAP1 in MSCs. We found that acute loss of YAP1 after apicidin treatment resulted in the mixed effects of transcriptional arrest and proteasomal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Although we demonstrated that nuclear PSME4 actively degraded acetyl-YAP1 in the nucleus in response to apicidin treatment [ 14 ], the fundamental role of PSME4 in the cardiac commitment of MSCs remains unclear. We isolated bone-marrow MSCs (BM-MSCs) from either Psme4 knock-out (KO) mice or wild-type littermates and tested the cellular characteristics of each genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we demonstrated that nuclear PSME4 actively degraded acetyl-YAP1 in the nucleus in response to apicidin treatment [ 14 ], the fundamental role of PSME4 in the cardiac commitment of MSCs remains unclear. We isolated bone-marrow MSCs (BM-MSCs) from either Psme4 knock-out (KO) mice or wild-type littermates and tested the cellular characteristics of each genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…1B–D ). When considering previous results [ 14 , 23 ], we assumed that the retardation of clearing of Yap1 in the nucleus was the responsible mechanism for delayed cardiac commitment. To answer the fundamental question, we employed the lentivirus-driven shRNA system in hTERT-MSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the two positively charged PA200 entry pores might not favor the binding of acetylated histones due to the predominance of positively charged histidine residues [ 4 , 9 , 10 ]. A very recent study showed that PA200 degrades acetylated-YAP1 in the in the nucleus of mesenchymal stem cells (MSC) in response to the histone deacetylase (HDAC) inhibitor apicidin [ 37 ]. The authors also injected PA200 KO MSCs into an infarcted heart to define the role of PA200 in myocardial infarction.…”
Section: Functionmentioning
confidence: 99%